Evolución de la facturación electrónica y su efecto en la recaudación de impuestos en Ecuador, periodo 2018-2022 - Rodriguez Lopez, Mishell Carolina (2024)
ABSTRACT: The objective of this research was to determine the evolution and effect of e-invoicing on tax collection in Ecuador during the period 2018 - 2022. Tax payments especially income tax, and value-added tax is an obligation of all companies with legal personality. This represents the main source of economic resources that allow the Ecuadorian State to maintain public savings. This research aims to establish the variations between the established periods, especially the Income Tax and the Value Added Tax, which represent the largest taxes in Ecuador. Non-experimental research was carried out, with a qualitative approach and descriptive design, the central axis of the study was constituted by the graphs presented on the variations between periods and provinces. Tax collections for the periods 2018 - 2022 were analyzed. The most significant results show the positive impact that e-invoicing has on tax collection. In conclusion, it´s shown that the technological mechanism established during the transition periods to comply with tax obligations through electronic invoicing represents a significant advance in efficiently collecting taxes in the country.